A "eucatástrofe" de J. R. R. Tolkien: a jubilosa estética literária da ideia transformada em conceito - Gomes, Emanuelle Garcia (2024)
This research aims to reflect and discuss the idea presented by J.R.R. Tolkien, in his essay entitled “On Fairy-Stories” (1964), of “Eucatastrophe” and transposing it as a concept. The term, coined by the author himself, refers to a situation of sudden change of events at the end of a story, as in fictional narratives, especially fantasy ones. It in general terms, it brings about a good ending for the protagonist, ensuring that he is not the victim of an unfortunate fate, as he is in the Tragedy. The concern that motivates this thesis is to deal with the effects of this idea within the fiction and fantasy compendium that Tolkien produced throughout his life and beyond, which may even serve as an appropriate technique for other narratives from other sources. The reception, both by the public and critics, of his works was very positive, to the point that he established himself as one of the best-known authors of the 20th century. In addition, his works continue to be organized and published in the 21st century, being adapted into several other media, such is the interest they still provide in the so-called “pop culture”. Setting Tolkien's theory on fairy tales and the update of his thinking in relation to the genre, as derived and expanded upon by G. K. Chesterton, this research intends to deepen the idea of “eucatastrophe”, defining it as a concept; to investigate to what extent it became a standard in his writing exercises, in narratives that reassemble stories from Middle-earth (or from other traditional myths); and finally, to check the characteristics of the Epic and Tragic genre in relation to Eucatastrophe. This theoretical discussion of the modes of writing is, a priori, based on Aristotelian studies, such as Ethics and Poetics, as well as the theory of the beautiful and sublime of romantic philosophers such as Immanuel Kant and Friedrich Schiller.